Israeli settlements : land politics beyond the Geneva Convention - Blecher, Martin, 1985- (Hamilton Books, 2018)
Few scholars have taken an interest in how Israel has rationalized and defended its settlement policies through its use of Ottoman land laws combined with the Hague Regulations. This book provides a descriptive study of Israel's land policies.